Affective and Normative Commitment as Intervening Variables of the Links between Ethical Leadership, Religiosity, and Fraud - Andrey Hasiholan Pulungan; Purwaka Adhitama; Albert Hasudungan; Basid Hasibuan (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
This study aims to examine the mediating effect of affective and normative commitments in the relationship between ethical leadership, religiosity, and fraud in Indonesia government institutions. Using the cluster sampling method, data was collected through surveys with respondents were employees of government agencies in Indonesia. The survey obtained 111 responses and the data were analyzed using path analysis. The findings revealed that ethical leadership and intrinsic religiosity have a direct negative effect on employees’ legal fraud engagement. However, only ethical leadership that indirectly and negatively affects employees’ legal fraud through affective commitment. The normative commitment does not mediate the effect of intrinsic religiosity to legal fraud engagement. Hence, this study provides evidence on the importance of the control environment as well as the presence of ethical leaders in government institutions.